2015
DOI: 10.4315/0362-028x.jfp-14-441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Allyl Isothiocyanate against Anisakis Larvae during the Anchovy Marinating Process

Abstract: Allyl isothiocyanate (AITC), is a natural compound found in plants belonging to the family Cruciferae and has strong antimicrobial activity and a biocidal activity against plants parasites. Anisakidosis is a zoonotic disease caused by the ingestion of larval nematodes in raw, almost raw, and marinated and/or salted seafood dishes. The aim of this work was to evaluate the effect of AITC against Anisakis larvae and to study its potential use during the marinating process. The effects of AITC against Anisakis lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This finding was in accordance with those of Vazirian et al, 37 which proved that the main compound of the cinnamon essential oil is (E)-cinnamaldehyde (Table 2). Two compounds were wileyonlinelibrary.com/jsfa Snoussi et al 38 Radaelli et al 39 Vazirian et al 37 Snoussi et al 40 Snoussi et al 40 Valero et al 41 Giarratana et al, 33 identified in the cardamom-flavored olive oil: 1,8-cineole (57.1%) and -terpinyl acetate (20.6%), with similar percentages to those reported in cardamom essential oil by Snoussi et al 38 ( Table 2). In the rosemary-flavored olive oil, the major compounds were 1,8-cineole (60.8%), -pinene (9.1%), camphor (7.9%), and camphene (6.8%).…”
Section: Volatile Fraction Compositions Of Spiced Oilssupporting
confidence: 54%
See 2 more Smart Citations
“…This finding was in accordance with those of Vazirian et al, 37 which proved that the main compound of the cinnamon essential oil is (E)-cinnamaldehyde (Table 2). Two compounds were wileyonlinelibrary.com/jsfa Snoussi et al 38 Radaelli et al 39 Vazirian et al 37 Snoussi et al 40 Snoussi et al 40 Valero et al 41 Giarratana et al, 33 identified in the cardamom-flavored olive oil: 1,8-cineole (57.1%) and -terpinyl acetate (20.6%), with similar percentages to those reported in cardamom essential oil by Snoussi et al 38 ( Table 2). In the rosemary-flavored olive oil, the major compounds were 1,8-cineole (60.8%), -pinene (9.1%), camphor (7.9%), and camphene (6.8%).…”
Section: Volatile Fraction Compositions Of Spiced Oilssupporting
confidence: 54%
“…All the encysted anchovy fillets were marinated in 100 mL of the typical industrial marinating solution (MS): 1:1 (vol/vol) of distilled water and vinegar (60 g L −1 acetic acid), 30 g L −1 NaCl and 10 g L −1 citric acid . Anchovy fillets were marinated for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, essential oils (EOs), aromatic oily liquids obtained from plant materials, are well known for their preservative properties. These substances and their components are used in food, pharmaceutical and cosmetic industries, for their antibacterial, antifungal, antiviral, nematocidal, anti-carcinogenic and antioxidant properties (Frassinetti et al , 2011; Giarratana et al , 2014, 2015a, 2015b; Rota et al , 2008; Silva-Angulo et al , 2015). Bergamot essential oil (BEO), extracted from the peel of Citrus bergamia Risso , is characterized by several of these properties (Navarra et al , 2016; Pernice et al , 2009; Sicari et al , 2015; Trombetta et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirms the presence of anisakid species with public health implications in lots of fishery products from different FAO areas. Although freezing condition and other treatments as salting and spicing assure no viable larvae in the fish products [40][41][42][43], the risk of allergens in the edible part of fish for hypersensitive individuals should be highlighted. EU legislation [44] recognizes that any parasitized fish under a visual inspection scheme should be unfit for human consumption.…”
Section: Safety and Quality Considerationsmentioning
confidence: 99%